Assessment of Community Knowledge, Attitude and Practices toward Bovine Tuberculosis in Jinka Town, Southern Ethiopia - Asrat Solomon Kenasew; Said Mohammed Harar; Alemitu Ketema Tamirat; Metadel Molto (East African Journal of Biophysical and Computational Sciences)
Bovine tuberculosis is yet a major public health problem throughout the world, including African countries like Ethiopia. Limited public knowledge about the disease, coupled with negative attitudes and poor health practices, are contributing to this issue. A crosssectional study was carried out from March 2023 to July 2023 to assess the community knowledge, attitude, and practice on Bovine Tuberculosis in Jinka Town. Questionnaire survey and retrospective data were used as a tool for data collection. Among 382 respondents, 254 (66.5%) knew about Bovine tuberculosis, whereas 128 (33.5%) respondents did not have any idea about the disease. Except sex, other predictors like age, marital status, educational level and occupation were significantly associated with knowledge and preventive practices towards Bovine tuberculosis. Respondents had misconceptions on zoonotic importance of the disease and 95 (24.87%) respondents consume raw milk. Regarding retrospective data result, among 1278 patients examined for Tuberculosis, 316 (24.7%) and 5 (0.39%) were positive for pulmonary and extra pulmonary Tuberculosis in 2020 G.C. During 2021 G.C, among 1066 patients examined for Tuberculosis, 190 (17.8%) and 12 (1.12%) patients were positive for pulmonary and extra pulmonary Tuberculosis respectively. Number of patients for pulmonary and extrapulmonary were increased to 18.25% and 4% respectively in 2022 G.C. Since there were misconceptions among the respondents, awareness creation and detailed investigation on the status of Bovine and human Tuberculosis was recommended.